PENGARUH TAX RETENTION RATE (TRR), BOOK TAX DIFFERENCES (BTD) DAN EFFECTIVE TAX RATE (ETR) TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Yoyo Sudaryo; Dyah Purnamasari; Nunung Ayu Sofiati; Astrin Kusumawardani; Tjipto Sajekti (Ekonam: Jurnal Ekonomi, Akuntansi & Manajemen, 2020)
ABSTRACT; One of the measurement of company performance is financial performance. Financial performance is a formal effort that has been made by a company that can measure the company's success in generating profits. Profit is the simplest measure to assess a company's financial performance. Financial performance will also provide an overview of the efficiency of the use of funds regarding the results of obtaining profits, which can be seen after comparing net income after tax. Taxes are costs that must be incurred by the company. Therefore, companies through management always strive to minimize taxes and this effort is often referred to as tax planning. This study aims to examine the effect of tax retention rate (TRR), book tax differences (BTD) and effective tax rate (ETR) on financial performance by using a proxy measure of Net Profit Margin (NPM). The method used in this research is descriptive verification with a quantitative approach. The data used is secondary data, data collection is done through documentation and literature research on property and real estate companies listed on the Indonesia Stock Exchange in 2012-2016 with a population of 46 companies. The number of samples in this study were 18 companies which were determined using purposive sampling. Data analysis to answer the problem formulation used: descriptive analysis, inferential statistics, classical assumption test, multiple linear regression test, correlation coefficient test, determination coefficient test, and hypothesis testing using partial test (t test) and simultaneous test (f test). Data processing using the SPSS application. Based on the results of the research on the t test, it was found that TRR had a positive effect on financial performance where the tcount value of 2.773 was greater than the t table of 1.987. BTD has a positive effect on financial performance where the tcount value of 3.784 is greater than the t table of 1.987.ETR has a positive effect on financial performance where the tcount of 2.627 is greater than the t table of 1.987. Based on the results of the research on the f test, it was found that TRR, BTD, ETR had a significant effect on financial performance where Fcount was greater than 6.770 was greater than F table 3.10. Keywords: Tax Retention Rate, Book Tax Differences, Effective Tax Rate, Financial Performance